`(dy)/dx = (6-x^2)/(2y^3)`

This differential equation is separable since it can be rewritten in the form

`N(y) dy=M(x) dx`

So separating the variables, the equation becomes

`2y^3dy = (6-x^2)dx`

Integrating both sides, it result to

`int 2y^3dy = int (6-x^2)dx`

`2*y^4/4 + C_1 = 6x-x^3/3 + C_2`

`y^4/2 + C_1 = -x^3/3 + 6x + C_2`

Since C1 and C2 represent any number, it can be expressed as a single constant C.

`y^4/2 = -x^3/3 + 6x + C`

**Therefore, the general solution of the given differential equation is `y^4/2 = -x^3/3 + 6x+ C` .**